Doing and undoing Caribou/Atiku: diffractive and divergent multiplicities and their cosmopolitical orientations*. Issue 1 (1st January 2018) - Blaser, Mario
ABSTRACT: More than one and less than many, has become a refrain to depict the notion of multiplicity. Borrowed from Mariyln Strathern, Annemarie Mol mobilized the refrain to succinctly capture the complex result of a series of operations that make a variety of practices hold together as a singular thing. In this article, I seek to explore some consequences of the proposition that multiplicity can be figured in, at least, two different ways: as diffraction, where the operations of singularization explored by Mol are more easily carried out, and as divergence, where singularization is not necessarily an option. The exploration is part of a larger project to rework the notion of cosmopolitics first proposed by Isabelle Stengers and later taken by Bruno Latour. Elsewhere I have argued that their conception of cosmopolitics as a project oriented towards the composition of a common world is predominantly informed by the figuration of multiplicity as diffraction, and thus it very much resembles a process of singularization writ large. In this context, foregrounding multiplicity as divergence opens a path to probe the limits of this conception of cosmopolitics, inquire into the different ways in which multiplicity holds together, and envision alternative forms of cosmopolitics. I organize my exploration around two entities caribou and atîku that, so to speak, occupy the same space at the same time in terms of bodily presence, albeit dominant common sense would have it that atîku and caribou are two words for the same entity.